Global Vaccine Action Plan lessons learned III: Monitoring and evaluation/accountability framework. Issue 33 (14th July 2020) - Cherian, Thomas; Hwang, Angela; Mantel, Carsten; Veira, Chantal; Malvolti, Stefano; MacDonald, Noni; Steffen, Christoph; Jones, Ian; Hinman, Alan
Highlights: The M&E/A framework was a critically important element of GVAP. It was a cyclical process of monitoring, review, and recommendations for action. Though a step in the right direction, it failed to hold all stakeholders accountable. Several GVAP goals were aspirational and unrealistic for many countries. Abstract: Introduction: The Monitoring & Evaluation/Accountability (M&E/A) framework of the Global Vaccine Action Plan (GVAP) was used to report progress annually to the World Health Assembly (WHA). Methods: Stakeholder feedback was obtained through five reviews consisting of surveys and semi-structured interviews conducted from 2017 to 2019. Participants consisted of individuals involved in the development and implementation of GVAP or its M&E/A process, national immunization managers, academics, representatives of non-governmental organizations, and civil society organizations. Results: The feedback was mixed and contradictory for some components, though most participants reported that the M&E/A process was a highlight of GVAP and a step in the right direction. Several of the goals and targets were considered aspirational and unrealistic for many countries. There were mixed responses on whether it promoted accountability, especially at the country level. Discussion: The mixed and contradictory views on the M&E/A processes and its impact suggested a failure of communication about its scope and intent. Though the process, especially the annual reporting to the WHA, kept immunization high on the global agenda, it failed to fully meet the expectations in promoting accountability. Engaging with countries to capture the local context in setting global goals and targets and promoting local M&E/A processes will be important to achieve accountability in the next decade.